Sodium vanadium phosphate electrode material with different non-crystallization degrees, electrode and battery preparation method

The preparation of sodium vanadium phosphate positive electrode materials with different degrees of amorphization through chemical synthesis and Joule heating device heating method, solving the problems of volume expansion, low ionic conductivity and unsatisfactory cycle life of the vanadium phosphate positive electrode materials during the cycle process, and achieving high electrochemical performance and stability of the material.

CN119551650APending Publication Date: 2025-03-04ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775341.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The volume expansion of sodium vanadium phosphate cathode material, low ionic conductivity and unsatisfactory cycle life during the cycle, resulting in poor Na+ diffusion capacity and short battery life, hindering its large-scale production and practical application.

Method used

The amorphous sodium vanadium phosphate positive electrode material with different degrees of amorphization was prepared by chemical synthesis method, and the amorphous material was prepared by rapid heating using Joule thermal device to regulate the proportion of amorphous regions to improve electrochemical performance.

Benefits of technology

It significantly improves the electrochemical properties of the material, enhances the Na+ diffusion ability, makes the material close to the theoretical specific capacity, stabilizes the structural framework, and improves the cyclic stability at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551650A_ABST
    Figure CN119551650A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, and discloses a preparation method of a sodium vanadium phosphate positive electrode material with different non-crystallization degrees, and the preparation method comprises the following steps: adding vanadium trioxide (V2O3) and citric acid into 20mL of deionized water, and stirring at 50-90 DEG C for 1-2 hours to obtain a blue solution; cooling to room temperature, respectively adding ammonium dihydrogen phosphate (NH4H2PO4) and sodium acetate (CH3CHOONa), and continuously stirring for 10-20 hours to obtain a uniform solution; finally, putting the solution into a drying oven at 50-90 DEG C, and drying to obtain powder; and wrapping a proper amount of the powder with graphite paper, putting the wrapped powder into a heating chamber of a Joule heating device, and performing pulse for 10-50 times to prepare the sodium vanadium phosphate positive electrode materials with different non-crystallization degrees. The sodium vanadium phosphate positive electrode materials with different non-crystallization degrees are prepared by using a Joule heat rapid heating device, the method is simple to operate, and the final product is rapidly and conveniently obtained. In addition, the method can be continuously operated, and large-scale synthesis can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a sodium vanadium phosphate electrode material, an electrode and a battery with different amorphization degrees. Background Art

[0002] The cost of lithium-ion batteries is high due to the small amount of lithium resources and their uneven distribution. Sodium ions are not only widely distributed but also abundant in resources. Most importantly, they are low in cost and safer. Sodium vanadium phosphate, a positive electrode material in polyanionic compounds in sodium-ion batteries, is considered to be one of the potential candidate positive electrodes to replace lithium-ion batteries in the future. Sodium vanadium phosphate will undergo V at a voltage of about 3.4V. 3+ / V 4+ The redox reaction has 117.6 mAhg -1 In addition, it has a stable framework and an open 3D sodium ion diffusion channel, but sodium vanadium phosphate itself has low conductivity and unsatisfactory cycle life, resulting in Na + Poor diffusion ability and short battery life seriously hinder the large-scale production and practical application of sodium vanadium phosphate positive electrode materials.

[0003] To address the above problems, the main methods are to carbon-coat sodium vanadium phosphate cathode materials or use other transition metals to partially replace vanadium elements to improve ionic conductivity and cycle stability. However, there is almost no mention of methods for amorphizing the sodium vanadium phosphate cathode. The introduction of amorphous can effectively buffer the volume expansion of the sodium vanadium phosphate cathode during the cycle; in addition, the presence of amorphous can also improve ionic conductivity, improve the electrochemical performance of the material, and be closer to the theoretical specific capacity. Summary of the invention

[0004] In order to solve the technical problems raised in the background technology, the present invention provides a method for preparing a sodium vanadium phosphate positive electrode material, an electrode and a battery with different degrees of amorphization.

[0005] The present invention is implemented by the following technical solution: a method for preparing sodium vanadium phosphate positive electrode materials with different degrees of amorphization, comprising the following steps:

[0006] Step 1, adding vanadium trioxide (V2O3) and citric acid to 20 mL of deionized water, stirring at 50-90° C. for 1-2 h to obtain a blue solution;

[0007] Step 2: After cooling to room temperature, add ammonium dihydrogen phosphate (NH4H2PO4) and sodium acetate (CH3CHOONa) respectively, and stir for 10 to 20 hours to obtain a uniform solution;

[0008] Step 3, finally, the solution is placed in an oven at 50-90°C to dry to obtain a powder;

[0009] Step 4: Then, a proper amount of powder is wrapped with graphite paper and placed in a Joule heat device heating chamber. After pulsing for 20 to 50 times, sodium vanadium phosphate positive electrode materials with different degrees of amorphization can be prepared;

[0010] Among them: the mass ratio of V2O3: citric acid: NH4H2PO4: CH3CHOONa is 2-3: 5-6: 5-7: 5-7.

[0011] Preferably, the selected gas is argon, the vacuum degree of the entire chamber of the Joule heating device is maintained at 0.01-0.05Mpa, the current is set at 100-200A, and the heating time is 90-180s.

[0012] Preferably, the mass ratio of V2O3: citric acid: NH4H2PO4: CH3CHOONa is 2.4: 5.4: 6.2: 6.2, and large-scale synthesis can be carried out by increasing their usage proportionately.

[0013] A sodium vanadium phosphate positive electrode material with different amorphization degrees is prepared by the above method.

[0014] The present invention also proposes a method for preparing a sodium vanadium phosphate electrode, comprising the following steps:

[0015] Weigh an appropriate amount of the above-mentioned sodium vanadium phosphate positive electrode material with different degrees of amorphization, mix it evenly with a certain amount of polyvinylidene fluoride (PVDF) and conductive carbon black, then add an appropriate amount of N-methylpyrrolidone (NMP) to obtain a uniform slurry, and then evenly apply the slurry on aluminum foil, dry it at 80°C and then cut it into discs with a diameter of 12 mm.

[0016] Preferably, the mass ratio of the materials is as follows: sodium vanadium phosphate: conductive carbon black: PVDF = 7:2:1

[0017] Preferably, the electrode coating has a thickness of 10 to 30 μm.

[0018] The invention provides a sodium vanadium phosphate electrode, which is prepared by adopting the above-mentioned electrode preparation method.

[0019] The present invention further proposes a method for preparing a sodium ion battery, comprising the following steps: placing a positive electrode shell, the electrode sheet according to claim 8, and a glass fiber diaphragm in a glove box filled with argon gas in sequence, adding an electrolyte, a Na metal sheet of appropriate size, a stainless steel gasket and a spring, and finally placing a negative electrode shell; then placing the assembled battery into a pneumatic sealing machine for compaction.

[0020] The sodium ion battery is prepared by the above-mentioned battery preparation method.

[0021] The present invention prepares sodium vanadium phosphate materials with different amorphization degrees. The sodium ion battery assembled with the materials has a reversible discharge capacity of 90 to 100 mAh g after 5000 cycles at a voltage range of 2.5 to 4.2 V and a rate of 20C. -1 , the capacity retention rate is between 90 and 100%.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a chemical synthesis method to prepare a precursor, and uses a Joule heat rapid heating device to prepare sodium vanadium phosphate positive electrode materials with different degrees of amorphization. This method is simple to operate, and the final product is obtained quickly and conveniently. In addition, this method can be operated continuously and can achieve large-scale synthesis.

[0024] 2. The sodium vanadium phosphate positive electrode material with different amorphization degrees prepared by the present invention determines the optimal amorphous / crystalline ratio by regulating the amount of amorphous regions. The existence of the optimal amorphous / crystalline ratio significantly improves the electrochemical performance of the material and improves the utilization of active substances.

[0025] 3. The sodium vanadium phosphate positive electrode material prepared by the present invention can significantly improve the Na+ diffusion capacity, making the material closer to the theoretical specific capacity, stabilizing the structural framework of the sodium vanadium phosphate, and further improving the cycle stability at high rates. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction (XRD) diagrams of sodium vanadium phosphate positive electrode materials with different degrees of amorphization prepared by the present invention are shown.

[0027] Figure 2 The following are scanning electron microscope (SEM) images of sodium vanadium phosphate positive electrode materials with different degrees of amorphization prepared by the present invention.

[0028] Figure 3 The high-resolution transmission electron microscope (HR-TEM) images of sodium vanadium phosphate positive electrode materials with different degrees of amorphization prepared by the present invention are shown.

[0029] Figure 4 The figures are X-ray photoelectron spectra (XPS) of sodium vanadium phosphate positive electrode materials with different degrees of amorphization prepared by the present invention.

[0030] Figure 5 It is a constant current charge and discharge curve diagram of sodium vanadium phosphate electrodes with different amorphization degrees prepared by the present invention at 0.2C.

[0031] Figure 6 The sodium vanadium phosphate electrode materials with different amorphous degrees prepared by the present invention have a 0.1mVs -1 ~1.0mVs -1Cyclic voltammetry (CV) curves at different scan rates.

[0032] Figure 7 The present invention discloses the cycle performance of sodium vanadium phosphate electrodes with different amorphization degrees prepared by the present invention at a rate of 20C.

[0033] Figure 8 The invention discloses the rate performance of sodium vanadium phosphate electrodes with different amorphization degrees at 1 to 50C.

[0034] Among them, the horizontal coordinate of the obtained XRD graph is the diffraction angle (2θ), and the vertical coordinate is the diffraction peak intensity (Intensity); the horizontal coordinate of the XPS graph is the binding energy (Bindingenergy), and the vertical coordinate is the intensity (Intensity); the horizontal coordinate of the obtained cyclic voltammetry curve is the voltage (Voltage), and the vertical coordinate is the current (Current); the cycle performance diagram and the rate performance diagram, the horizontal coordinate is the cycle number (Cyclenumber), and the vertical coordinate is the specific capacity (Specificcapacity); the obtained charge and discharge curve diagram, the horizontal coordinate is the specific capacity (Specificcapacity), and the vertical coordinate is the voltage (Voltage). DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0036] The chemical reagents used in the present invention are all analytically pure vanadium pentoxide, citric acid, ammonium dihydrogen phosphate, and sodium acetate. The purity of the inert gas (argon) used in step 1 is 99.999%. The aluminum foil and glass fiber diaphragm used in Example 2 were purchased from Suzhou Duoduo Chemical Technology Co., Ltd.

[0037] Example 1: Step 1, synthesis of precursor: weigh 2.4g of vanadium trioxide, 5.4g of citric acid, pour into a beaker and add 20mL of deionized water, continue heating at 50-90°C for 1-2h to obtain a blue solution; then cool to room temperature and add 6.2g of ammonium dihydrogen phosphate and sodium acetate respectively, continue stirring for 12-20h to obtain a uniform solution. Finally, pour the solution into a petri dish and put it into a 50-90°C oven for evaporation for 6-10h to obtain a precursor powder. Preparation of positive electrode material: Wrap the obtained precursor with graphite paper, then put it into a Joule heat device to heat the chamber, use argon gas to exhaust the air in the chamber, set the fast mode, set the current to 100-200A, the heating time to 90-180s, and pulse 20-510 times to obtain sodium vanadium phosphate positive electrode materials with different degrees of amorphization. Wash the obtained material with ethanol and deionized water several times to obtain the final product.

[0038] Example 2: Preparation of electrode materials: Weigh 140 mg of sodium vanadium phosphate positive electrode material in step 1 above, and then weigh 40 mg of conductive carbon black and 20 mg of PVDF respectively, mix them evenly, then add an appropriate amount of NMP to mix into a uniform slurry, and finally evenly apply the slurry on aluminum foil to prepare an electrode. Keep the thickness of the slurry applied on the aluminum foil at 10 to 30 μm. Put the coated aluminum foil into a vacuum drying oven at 80°C and dry it for 12 hours, and cut the dried electrode into discs with a diameter of 12 mm. The negative electrode is a sodium metal sheet with a diameter of 14 mm.

[0039] Example 3: Assembly of sodium ion battery: The electrode obtained in step 2 is moved into a glove box filled with argon, and the water content and oxygen content in the glove box are all below 0.01ppm. During assembly, the electrode obtained in step 2 is placed in the positive electrode shell of CR2032, and 100-200μL of 1MNaClO4 electrolyte containing ethylene carbonate (EC)-propylene carbonate (PC) (volume ratio of 1:1) and 5% fluoroethylene carbonate (FEC) by volume is added, followed by a glass fiber diaphragm with a diameter of 20mm, a sodium metal sheet, a stainless steel gasket and a shrapnel, and finally a negative electrode shell. The above-assembled battery is placed in a pneumatic sealing machine for air sealing, the purpose of which is to compress the battery. The assembled CR2032 sodium ion battery is tested for charge and discharge, cycle performance and rate performance. The charge and discharge tests of all batteries in the first three cycles are carried out at 0.2C, and then the electrochemical performance tests are not carried out at different rates according to different requirements. The test voltage range of the whole process is 2.5-4.2V. The charge and discharge curve of the electrode in the third cycle at 0.2C is as follows Figure 5 The capacity retention rate of the electrode at 20C is as follows: Figure 7 The performance of the electrode at different rates is as follows Figure 8 .

[0040] Results Analysis

[0041] As attached Figure 1 As shown, analysis of the material using XRD shows that it has good crystallinity, which is consistent with the reported R-3C space group structure of sodium vanadium phosphate.

[0042] As attached Figure 2 As shown, the scanning electron microscopy results show that the material has a more porous structure, which can better promote the wetting of electrode materials and electrolytes and improve the electrochemical performance.

[0043] As attached Figure 3As shown in the figure, the high-resolution transmission electron microscopy results clearly show the lattice fringes, and the amorphous regions can also be observed, which is consistent with the XRD pattern and shows good crystallinity. The presence of an appropriate amount of amorphous regions can improve the electrochemical performance of the material and improve the structural stability of the positive electrode material.

[0044] As attached Figure 4 As shown, the X-ray photoelectron spectroscopy results further prove that the sodium vanadium phosphate positive electrode material prepared by the present invention is successfully synthesized.

[0045] As attached Figure 5 and 6 As shown, the electrode shows a typical charge-discharge platform during the charge-discharge process, where the platform is V 3+ / V 4+ Redox reaction. The initial third cycle charge-discharge curve of the electrode at 0.2C shows a discharge capacity of 111.88 mAh g -1 , close to the theoretical specific capacity, indicating that the sodium vanadium phosphate positive electrode materials with different amorphization degrees prepared by the present invention have improved the Na+ diffusion capacity. Figure 6 The cyclic voltammograms can also further illustrate the redox reaction of the battery working with a typical sodium vanadium phosphate electrode.

[0046] As attached Figure 7 As shown, the electrode has a discharge capacity of 89.84 mAhg at 20 C. -1 The initial capacity of the material has no obvious attenuation after 5000 cycles, and the post-cycle capacity is as high as 90.55 mAh g-1, which further emphasizes that the material prepared by the present invention not only has a high Na + Diffusion ability, but also can stabilize the frame structure and improve the cycle life of the battery.

[0047] As attached Figure 8 As shown in Figure 2, the discharge capacity of the battery at different rates of 1 to 50C is 108.52, 105.59, 104.6, 101.32, 98.03 and 91.49 mAh g -1 , when the current returns to 1C, it still has 108.45mAhg -1 The discharge specific capacity of the material prepared by the present invention has good structural stability.

[0048] Therefore, it can be concluded from the experimental data that the present invention improves the cycle stability by adjusting the amount of amorphous region of the sodium vanadium phosphate positive electrode material. In addition, adjusting the ratio of amorphous / crystalline regions can improve both the cycle stability and the Na +The diffusion capacity of the material is further close to the theoretical specific capacity. The charge and discharge curves of the embodiment and the comparative example, the cycle stability at high rate and the rate performance are better than those of the comparative example, showing excellent electrochemical performance. Therefore, the sodium vanadium phosphate positive electrode material with different amorphization degrees proposed by the present invention is feasible and can improve the electrochemical performance.

[0049] The present invention provides a method for preparing sodium vanadium phosphate positive electrode materials with different amorphization degrees, which is simple to operate, time-saving and labor-saving, has low energy consumption, and can be synthesized in large quantities. The prepared material has the advantages of high discharge specific capacity and high cycle stability, and provides a new idea and method for the preparation of sodium vanadium phosphate positive electrode materials.

[0050] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing sodium vanadium phosphate positive electrode materials with different degrees of amorphization, characterized in that: The steps include: Step 1, add vanadium trioxide and citric acid to 20 mL of deionized water, stir at 50-90° C. for 1-2 hours to obtain a blue solution; Step 2, after cooling to room temperature, add ammonium dihydrogen phosphate and sodium acetate respectively, and stir for 10 to 20 hours to obtain a uniform solution; Step 3, finally, the solution is placed in an oven at 50-90°C to dry to obtain a powder; Step 4: Then, a proper amount of powder is wrapped with graphite paper and placed in a Joule heat device heating chamber. After pulsing for 20 to 50 times, sodium vanadium phosphate positive electrode materials with different degrees of amorphization can be prepared; Wherein: the mass ratio of vanadium trioxide: citric acid: diammonium dihydrogen phosphate: sodium acetate is 2-3:5-6:5-7:5-7.

2. The method for preparing sodium vanadium phosphate materials with different amorphization degrees according to claim 1, characterized in that: The selected gas is preferably argon, the vacuum degree of the entire chamber of the Joule heat device is maintained at 0.01-0.05Mpa, the current is set at 100-200A, and the heating time is 90-180s.

3. The method for preparing sodium vanadium phosphate electrode materials with different degrees of amorphization according to claim 1, characterized in that: The mass ratio of vanadium trioxide: citric acid: ammonium dihydrogen phosphate: sodium acetate is 2.4: 5.4: 6.2: 6.

2. Large-scale synthesis can be carried out by increasing their usage proportionately.

4. A sodium vanadium phosphate material with different degrees of amorphization, characterized in that: The method is prepared by the method according to any one of claims 1 to 3.

5. A method for preparing sodium vanadium phosphate materials with different degrees of amorphization, characterized in that: The steps include: Weigh an appropriate amount of the sodium vanadium phosphate positive electrode material as described in claim 3, mix it evenly with a certain amount of polyvinylidene fluoride and conductive carbon black, then add an appropriate amount of N-methylpyrrolidone to obtain a uniform slurry, and then evenly apply the slurry on aluminum foil, dry it at 80°C, and then cut it into discs with a diameter of 12 mm.

6. The method for preparing the sodium vanadium phosphate electrode according to claim 5, characterized in that: The mass ratio of the materials is as follows: sodium vanadium phosphate: conductive carbon black: polyvinylidene fluoride = 7:2:

1.

7. The method for preparing the sodium vanadium phosphate electrode according to claim 5, characterized in that: The electrode coating has a thickness of 10 to 30 μm.

8. A sodium vanadium phosphate electrode, characterized in that: The method is prepared by the method according to any one of claims 5 to 7.

9. A method for preparing a sodium ion battery, characterized in that: The method comprises the following steps: placing a positive electrode shell, the electrode sheet according to claim 8, and a glass fiber diaphragm in a glove box filled with argon gas in sequence, adding an electrolyte, a Na metal sheet of appropriate size, a stainless steel gasket and a spring, and finally placing a negative electrode shell; and then placing the assembled battery into a pneumatic sealing machine for compaction.

10. A sodium ion battery, characterized in that Prepared by the method as claimed in claim 9.